Tracing the Path Toward Self-Regulated Revision: An Interplay of Instructor Feedback, Peer Feedback, and Revision Goals - Li, Wentao; Zhang, Fuhui (Frontiers in Psychology, 2021)
Building upon Zimmerman’s socio-cognitive view of self-regulation, we explored EFL (English as a Foreign Language) students’ revision and the likely contribution to revision from three salient self-regulating sources: peer feedback, instructor feedback, and revision goals. Data was obtained from 70 Chinese EFL students in a writing class through a 300-word online writing assignment involving online instructor and peer feedback, free-response revision goals, and a required revision. We closely coded students’ revision and then used the same coding scheme to analyze the relative levels of association of revision changes with peer comments, instructor comments and revision goals. We found that: a) the majority of revision changes have been triggered by three mediating sources, with revision goals as the most significant contributing source. Additionally, most revision changes come from a combination of two or three sources, with the overlap of peer feedback and revision goals accounting for the biggest overlapping contribution for both high and low-level revisions; b) as for the relationship among the three sources, no significant difference was found between revision goals’ overlap rate with peer feedback and their overlap rate with instructor feedback. Instructor feedback and peer feedback did not overlap very much. Findings suggest that students could revise beyond instructor and peer feedback in their revision efforts guided by their own reflective goals, and peer feedback could function as a more productive and multiple-reader source of revision in comparison with instructor feedback. This study also provided evidence for students’ self-regulated learning of writing through the use of self-regulating resources and charted a route for how writing could be improved.